Development of qPCR platform with probes for quantifying prevalent and biomedically relevant human gut microbial taxa. (August 2020) - Kurina, Irina; Popenko, Anna; Klimenko, Natalia; Koshechkin, Stanislav; Chuprikova, Liubov; Filipenko, Maxim; Tyakht, Alexander; Alexeev, Dmitry
Abstract: Nowadays the advent of innovative high-throughput sequencing allows obtaining high-quality microbiome profiling. However, PCR-based tests are still considered the "golden standard" for many clinical applications. Here, we designed a qPCR-based platform with fluorescent-labeled oligonucleotide probes for assessing human gut microbiome composition. The system allows conducting qualitative and semiquantitative analysis for 12 prokaryotic taxa that are prevalent in the human gut and associated with diseases, diet, age and other factors. The platform was validated by comparing microbiome profile data obtained with two different methods - the platform and high-throughput 16S rRNA sequencing - across 42 stool samples. The test can form the basis for precise and cost-efficient microbiome assay for large-scale surveys including clinical trials with interventions related to diet and disease risks. Highlights: The qPCR platform provides semiquantitative analysis for 12 microbial taxa prevalent in the human gut. Comparison with high-throughput 16S rRNA sequencing of stool samples showed a high correlation between the methods. The platform is a promising method for the assessing links of microbiome composition to diet, diseases and other factors.